1998
DOI: 10.1152/jn.1998.79.6.3272
|View full text |Cite
|
Sign up to set email alerts
|

Signal Timing Across the Macaque Visual System

Abstract: The onset latencies of single-unit responses evoked by flashing visual stimuli were measured in the parvocellular (P) and magnocellular (M) layers of the dorsal lateral geniculate nucleus (LGNd) and in cortical visual areas V1, V2, V3, V4, middle temporal area (MT), medial superior temporal area (MST), and in the frontal eye field (FEF) in individual anesthetized monkeys. Identical procedures were carried out to assess latencies in each area, often in the same monkey, thereby permitting direct comparisons of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

84
622
6
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 933 publications
(732 citation statements)
references
References 38 publications
84
622
6
4
Order By: Relevance
“…Thirdly, crosscorrelation analysis revealed that the mean response latency in Area 17 was slightly earlier than that observed in Area 18 and significantly earlier than responses in Area 19 (Pb.01). This trend is consistent with a recent study where visual stimuli were presented to subjects (selected for clinical purposes) with subdural electrodes implanted over different regions of the visual cortex [36], as well as with signal arrival times recorded across distinct visual regions in nonhuman primates [37]. Taken together, these EEG source imaging results indicate that the artifact-correction methodology correctly identified and removed unwanted nonneural components of the EEG signal while preserving those containing information which reflected the movie stimulus.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, crosscorrelation analysis revealed that the mean response latency in Area 17 was slightly earlier than that observed in Area 18 and significantly earlier than responses in Area 19 (Pb.01). This trend is consistent with a recent study where visual stimuli were presented to subjects (selected for clinical purposes) with subdural electrodes implanted over different regions of the visual cortex [36], as well as with signal arrival times recorded across distinct visual regions in nonhuman primates [37]. Taken together, these EEG source imaging results indicate that the artifact-correction methodology correctly identified and removed unwanted nonneural components of the EEG signal while preserving those containing information which reflected the movie stimulus.…”
Section: Discussionsupporting
confidence: 90%
“…For comparison, consider that the average response latency in macaques' V1 ranges from 60 to 80 ms and the response to face stimuli occur around 100-150 ms post stimulus onset (Lamme & Roelfsema, 2000;Schmolesky et al, 1998). According to the authors, superior colliculus neurons filter face-like patterns with short latency to enable rapid processing of coarse facial information, while stimulus categorization develops in later processing phases through feedback from upstream areas.…”
Section: Timing and Speed Of Processing Along The Subcortical Pathwaymentioning
confidence: 99%
“…Axonal delays were chosen to be consistent with both known transmission delays in cortical and subcortical areas, and with the spatial conformation of the model, and are summarized in Supplementary Table 3 online. In general, inhibitory to excitatory connections have small delays, intra-cortical feedforward connections have longer delays (Dinse and Kruger, 1994), and feedback connections (both corticocortial and corticothalamic) have even longer delays (Schmolesky et al, 1998;Miller, 1996). The model accounts for the driving vs. modulatory nature of synaptic connections by exploiting both the magnitude of the synaptic weight and the passive neuron cable properties.…”
Section: Neurotransmitter Releasementioning
confidence: 99%